Ausnahmezustände: Zur Soziologie einer Gesellschaftsverfassung - Kretschmann, Andrea; Legnaro, Aldo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
A state of exception seems to be ubiquitous in our days. However, a distinction should be made between the legal form (state of exception in the first order) and the exceptionality of everyday control techniques (state of exception in the second order). An awareness of these varieties of states of exception allows for an analysis of mutual influences and their respective p